Overall Drilling Effectiveness: key performance indicator adapted for rock drilling (Research, Society and Development, 2023)
OEE (Overall Equipment Effectiveness) is a key performance indicator (KPI) widely used in performance analysis in the mining industry. The present study develops the ODE indicator (Overall Drilling Effectiveness) adapting OEE concept for the reality of diamond drilling. The product of availability, utilization and quality rates in the drilling process calculates ODE. Quality is defined by the quotient between recovered drill core metreage and total drilling advance metreage. ODE consists of a management numeric tool when confronted with productivity results and drilling equipment cost. In this case study of Pilar Mine, property of Jaguar Mining Inc., the 21% rate portrays the minimum acceptable ODE value considering the enterprise operational reality according to its geological, logistical and financial particularities. When the ODE rate approaches or exceeds this value, productivity increase and cost reduction per drilled metreage are noted. The adaptation of OEE concept and elaboration of ODE as a new performance indicator, intended directly for diamond drilling process, displays as a useful performance control tool. The utilization of ODE as a KPI provides the opportunity to manage operational productivity and financial performance simultaneously.